Implementación de una red de sensores para la medición de la calidad de aire y niveles de ruido en entornos abiertos de la ciudad de Loja. - Obaco Medina, Milto Ronaldo (2024)
The present degree project addresses acoustic and atmospheric pollution, topics considered a priority by the World Health Organization. Bibliographic research is conducted covering the study of gases such as CO, SO2, O3, NO2 and PM, as well as wireless communication, focusing on LPWAN technologies, specifically LoRa (Long Range), as a tool for radio links. In addition, the use of LoRa-compatible IoT platforms for pollution data management is explored. The calculations employed include propagation models in radio links and sensor calibration formulas using specialized software for simulations and obtaining constant values. The main objective is to obtain accurate data on pollution in the downtown area of the city of Loja, following WHO guidelines. For this, strategic locations are identified to implement nodes with specialized sensors in each pollutant variable, considering power levels and availability as key criteria for the location of these nodes. The research proposes to establish an efficient and reliable sensor network to monitor and collect accurate data on environmental pollution. With these results, it seeks to contribute to informed decision-making and the implementation of appropriate measures to mitigate the effects of pollution in the city. Keywords: Sensor network, air quality, air pollution, noise, sensors, wireless communication.